11 Towards international federated health data analysis: experience with the 4CE consortium for characterisation of Covid-19. (30th November 2020) - Spiridou, Anastassia; Booth, John; Issitt, Richard; Shah, Mohsin; Bryant, William; Sebire, Neil J
Abstract : The Covid-19 pandemic necessitated collaborations from hospitals around the world to improve knowledge and find suitable treatments. Responding to the quick spread of the virus, an international consortium was formed (4CE, https://covidclinical.net/) to rapidly collect data from the Electronic Patient Records (EPRs) of participating hospitals and publish results. The Digital Research Environment (DRE) enabled GOSH to join the consortium as one of the lead contributors of paediatric Covid-19 data in Europe and the only hospital in the U.K. The objective was to develop methods that ensure quick data collection and analysis using a mixed model of federated and centralised data analysis, and publish results on the clinical characterisation of Covid-19 in both children and adults to inform care and research. Building on the DRE's automated data integration processes and flows from the GOSH EPR system, we developed methods to semi-automate our Covid-19 cohort identification, restructure and harmonise our data to the internationally agreed specification and standards, perform quality control collaboratively, produce aggregate-level data using summary statistics, validate severity, and incorporate appropriate obfuscation of results. GOSH IG approval was obtained before sharing summary data with 4CE for further analysis. We were able to rapidly develop suitable technical and governance solutions as a first step towards federated health data analysis in an international collaborative of hospitals. The consortium analysis results, currently being submitted for publication, clinically characterise Covid-19 at an international level informing care and research. 4CE offers a new model of collaborative health data analysis based on the use of EPRs and federated analysis to respond quickly to pandemics like Covid-19. The use of GOSH DRE enabled our participation in the 4CE consortium and quick generation of collaborative data analysis results on Covid-19 paving the way for further development of advanced international federated health data analytics using EPRs.